Garbhagriha (sanctum sanctorum) of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
To the east, there is the main garbhagriha (sanctum sanctorum) accessible via the antarala (vestibule or antechamber). The dvarashakha (doorframe) of this sanctum is crafted by featuring multiple sections and adorned with sculptures of davarapalas (door guardians) and women holding kalashas (pitchers). Although the lalatabimba (lintel) of the doorframe displays a seated figure, its condition is not well preserved. Positioned above the lintel, the entablature showcases Natesha at the center.